6t+3t=6

Simple and best practice solution for 6t+3t=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6t+3t=6 equation:


Simplifying
6t + 3t = 6

Combine like terms: 6t + 3t = 9t
9t = 6

Solving
9t = 6

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Divide each side by '9'.
t = 0.6666666667

Simplifying
t = 0.6666666667

See similar equations:

| 10x+3=7x-39 | | -2(x+11)=6 | | .25y+3=-5 | | 5x+1=-2-8 | | -2.89=1.7 | | 6y+3(5y-19)-(y+2)=-142 | | 10=3+2 | | 24=-6m | | 0.25+.20x+1=2.25 | | F(a)=20 | | 2(x+2)-3(2x+5)=5 | | 7d=14 | | 2+3(p+3)=21 | | 3x-2=44 | | 4g+4=2g+12 | | 4b^2-49g^2=0 | | x^3+7x^2-25x-150=x^2 | | .50x+.50x=x+1 | | (4x+2)-(12x+8)+10x-3=6+11 | | 8x-1=2x-37 | | 4=2(y-5)-2 | | .4x-9=-7 | | (2x-7)(4x+12)=0 | | 5T=2T-12 | | 22+4x-14=0 | | -5.5=t+2 | | f(10)=100.3 | | 8x-3=4x+21 | | 3(2x-3)+3(3)=-7x | | 10x-.375-4x=6x | | 3a+1=-3(a-1) | | 6y+8y=10y |

Equations solver categories